2023
DOI: 10.3389/fendo.2023.1143835
|View full text |Cite
|
Sign up to set email alerts
|

Age-related modifications in CYP-dependent drug metabolism: role of stress

Abstract: Accumulating clinical evidence indicates extensive inter-individual variations in the effectiveness and adverse effects of standard treatment protocols, which are largely attributed to the multifactorial regulation of the hepatic CYP-dependent drug metabolism that is connected with either transcriptional or post-translational modifications. Age and stress belong to the most important factors in CYP gene regulation. Alterations in neuroendocrine responses to stress, which are associated with modified hypothalam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 161 publications
1
2
0
Order By: Relevance
“…We also previously observed this and have shown that PTEN signaling is increased in aging and inhibits TLR responses [ 16 ]. Several pathways related to the degradation of sugars, melatonin, etc., that involve cytochrome P450 proteins were downregulated with age, which is in keeping with the age-associated decrease in drug metabolism reported in previous studies [ 70 ].…”
Section: Discussionsupporting
confidence: 90%
“…We also previously observed this and have shown that PTEN signaling is increased in aging and inhibits TLR responses [ 16 ]. Several pathways related to the degradation of sugars, melatonin, etc., that involve cytochrome P450 proteins were downregulated with age, which is in keeping with the age-associated decrease in drug metabolism reported in previous studies [ 70 ].…”
Section: Discussionsupporting
confidence: 90%
“…Some susceptibility manifestations might result from the variations in cytochrome P450 enzyme activity due to genetic polymorphisms of CYP genes (Kekic, 2023). Cytochrome P450 isoenzymes were the main determinants of the pharmacokinetic properties of antidepressant drugs (Konstandi and Johnson, 2023). Piatkov et al reported that the response to uoxetine might vary among individuals even at therapeutic dosage because of the genetic polymorphisms of the isoenzymes encoding drug metabolism (Irina Piatkov et al, 2017),.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evaluation of drug posology selection, there is variation among individuals in drug response as a result of many different parameters associated with different factors including genomic [16][17][18][19][20], immunological [20,21], pharmacological [22,23] and toxicological variations [24,25], as well as interactions with drugs, dietary substances, etc. Similarly, there are also differences among individuals in drug response as a result of many other limitations such as underlying disease pathological complications, variations in organ functioning, idiosyncratic reactions, accessibility to effective drug posology due to high cost and other variations [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%